2020
DOI: 10.1002/chem.202001547
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Ion‐Functionalized CoS with Hexagonal Bipyramid Structures from a Metal–Organic Framework: Bifunctionality towards Supercapacitors and Oxygen Evolution Reaction

Abstract: To solve energy-related environmental problems and the energy crisis, efficient electrochemical materials have been developed as alternative energy storage and conversion systems. Abundant transition metalsa nd their sulfides are attractive electrochemical materials. Herein, we report an efficient phosphorization strategy,w hich improves the overall electrochemical performance of metal sulfides. In detail, CoS hexagonal bipyramids were synthesized through simple calcination combined with in situ sulfurizationo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 50 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…16 However, the wholesale application of Ir and Ru-based TMOs is considerably hindered by their exorbitant costs, harmful effects on the environment, limited availability, and inferior durability. 13,17,18 catalysts. Among different electrolysis assemblies (alkaline water electrolysis (AWE) and proton exchange membrane water electrolysis (PEMWE)), the anion exchange membrane (AEM) water electrolyzer exhibits the immense capability for producing highly pure hydrogen at a reasonable price using an anion exchange membrane as a solid polymer-based electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 However, the wholesale application of Ir and Ru-based TMOs is considerably hindered by their exorbitant costs, harmful effects on the environment, limited availability, and inferior durability. 13,17,18 catalysts. Among different electrolysis assemblies (alkaline water electrolysis (AWE) and proton exchange membrane water electrolysis (PEMWE)), the anion exchange membrane (AEM) water electrolyzer exhibits the immense capability for producing highly pure hydrogen at a reasonable price using an anion exchange membrane as a solid polymer-based electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ding et al studied the anion-dependent EWS characteristics of nickel foam (NF)-supported Zn–Ni–Co–M nanoneedle arrays (where M = oxide (O), P, S, and Se) and observed that Zn–Ni–Co–P and Zn–Ni–Co–S achieved the lowest overpotential values for the HER and OER, respectively . Jiang et al prepared phosphate ion-incorporated CoS to improve the supercapacitive and OER performance of CoS . Guo et al reported a dual-ligand synergetic modulation method to boost the energy storage performance of Ni–Co–A (where A = Se, P, and S) by partially doping Se, P, and S in Ni–Co hydroxide precursor arrays .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CoS 2 @BP‐COP affords the highest catalytic activity with an ultralow overpotential of 270 mV to deliver a current density of 10 mA cm −2 (Figure 4b). This value is much lower than that of the as‐prepared CoS 2 (319 mV), commercially available RuO 2 (351 mV), vulcanized BP‐COP (BP‐COP‐S, 432 mV), and nickel foam (NF) current collector (487 mV), and other reported cobalt sulfides based electrocatalysts (normally 285∼340 mV) [3a,8a,9b,d] . Tafel slopes were calculated based on LSV to study the reaction kinetics of corresponding electrocatalysts for OER.…”
Section: Resultsmentioning
confidence: 96%